Rozproszeni po swiecie : obozy i osiedla uchodzcow polskich ze Zwiazku Sowieckiego 1942-1950 - Wrobel, Elzbieta; Wrobel, Janusz (Chicago : Panorama Pub. Co., 1992)
Describes life for Polish refugees in the Soviet Union during the Second World War.
Summary in English.
Errata included.
Includes bibliographical references (p. 254-256) and indexes.
Keywords: Polish people -- Foreign countries -- History; Refugees -- Soviet Union; World War, 1939-1945 -- Deportations from Poland; Soviet Union -- Emigration and immigration